MENDUKUNG KEGIATAN DI TAMAN KANAK-KANAK MELALUI “AYO BERBAGI DENGAN SESAMA” - Kartika Nuringsih; Valentino Chandrawinata (Jurnal Bakti Masyarakat Indonesia, 2022)
The Covid-19 pandemic hasn't ended yet, even the Omicron variant has followed, thus prolonging the condition of people facing economic or social problems. This situation occurs throughout Greater Jakarta so that learning is carried out with limited face-to-face activities, as well as kindergartens which are carried out by learning from home. This also happened at the Kindergarten School or RA Taufiqurrahman Depok. In a pandemic situation, the community faced obstacles, so social activities were carried out with the aim of educating children at RA Taufiqurrahman in Beji Timur Depok about the importance of sharing with others. Moreover, in the month of Ramadan, children are taught to be grateful for the blessings of Allah SWT by sharing. The school faced limitations because for almost two years the activities did not run normally. Partner problems during the pandemic were related to limitations in conducting social education for children, so collaboration with external parties was needed to organize social-themed activities. This activity aims to avoid consumerism where children are taught to save and then set aside some of their savings to help others. The activity was realized through mentoring and practice on April 12-13, 2022, attended by 25 children with the principal and 3 accompanying teachers as well as Bank BRI Agro Niaga partners who had previously partnered in community service activities. Through this activity, children get the message of the importance of sharing. Then concrete steps were taken for the children to give gifts to the orphans, parents and the poor as many as 50 gifts. Children are involved in these activities in order to experience firsthand how they can share or help others. With the support of parents, it is hoped that children will be interested in social activities in their adulthood so that they will also support the formation of the character of Indonesian children who care for others or help each other. ABSTRAK: Pandemi Covid-19 belum berakhir bahkan varian Omicron menyusul sehingga memperpanjang kondisi masyarakat menghadapi masalah ekonomi atau sosial. Situasi tersebut terjadi di seluruh Jabodetabek sehingga pembelajaran dilakukan dengan tatap muka terbatas, demikian juga taman kanak-kanak dilakukan dengan cara belajar dari rumah. Hal juga terjadi pada Sekolah Taman Kanak-Kanak atau RA Taufiqurrahman Depok. Dalam situasi pandemi masyarakat menghadapi kendala sehingga dilakukan kegiatan sosial dengan tujuan mengedukasi kepada anak-anak di RA Taufiqurrahman di Beji Timur Depok tentang pentingnya berbagi dengan sesama. Terlebih lagi di bulan bulan Ramadhan anak-anak diajarkan mensyukuri rahmat Allah SWT dengan cara berbagi. Sekolah menghadapi keterbatasan karena hampir selama dua tahun kegiatan tidak berjalan secara wajar. Permasalahan mitra selama masa pandemi berkaitan dengan keterbatasan melakukan edukasi sosial kepada anak-anak sehingga sangat memerlukan kolaborasi dengan pihak eksternal untuk menyelenggarakan kegiatan bertemakan sosial. Kegiatan ini bertujuan menghindari konsumerisme dimana anak-anak diajarkan menabung kemudian menyisihkan sebagian tabungannya untuk membantu sesama. Kegiatan direalisasikan melalui pendampingan dan praktek pada 12-13 April 2022 diikuti 25 anak-anak dengan kepala sekolah dan 3 guru pendamping serta mitra Bank BRI Agro Niaga sebelumnya sudah berpartner dalam kegiatan pengabdian. Melalui kegiatan ini anak-anak mendapatkan pesan pentingnya berbagi. Kemudian dilakukan langkah nyata anak-anak memberikan bingkisan diberikan kepada yatim-piatu, orang tua dan fakir miskin sebanyak 50 bingkisan. Anak-anak dilibatkan dalam kegiatan tersebut supaya merasakan secara langsung bagaimana dapat berbagi atau membantu orang lain. Dengan dukungan orang tua diharapkan anak-anak tertarik dengan kegiatan sosial di masa dewasanya nanti sehingga turut mendukung pembentukan karakter anak Indonesia peduli kepada sesama atau tolong menolong.